Inserción en el mercado laboral de los graduados de Comunicación Social de la UPS - Rivera Chamorro, Rommel Fernando (2018)
This research is based on a qualitative and quantitative analysis, which allowed us to make valid inferences regarding the process of labor insertion of communication graduates from the Universidad Politécnica Salesiana. This research was constructed with the purpose of demonstrating the adequate parameters, which allow to identify which are the most important factors, by means of that particularity, the communicator can take into consideration the factors of better influence in his incorporation to the labor world. The analysis comes from a virtual survey conducted by the Salesian Polytechnic University, with a total population 2012 graduated until March 2017, the sample responds to 684 people representing 34% of the global stable. The survey shows a total of 161 questions, of which 31 are considered determining factors, and are divided into 6 sections, in addition to the participation of two communication professionals, in the form of in-depth interviews, with which was made the present analysis. The research allowed us to identify a new form of employability known as entrepreneurship, which is also one of the great challenges facing the communicator after the university, here the viability of this new alternative can be demonstrated, which is based on from the new forms of communication called micromedia.